The Role Of Sales Growth and Profitability in Determining Capital Structure - Suriani, Seri; Nur, Indrayani; Moridu, Irwan; Bakri, Asri Ady; Tasrim, Tasrim (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
The objective of the research is to identify the effect of growth in sales and profitability on capital structure. The research object is the sub-consumer goods manufacturing industry on the IDX 2018-2022. This type of research is quantitative research. Data collection uses purposive sampling procedures. This research uses information from the IDX. The research results prove that partially proves that sales growth has a positive effect on capital structure, meaning that if sales growth increases, then the capital structure will be more appropriate. Profitability has a positive impact on capital structure, meaning that if profitability increases, the capital structure is more appropriate. Sales growth and profitability simultaneously have a positive effect on capital structure, meaning that if sales growth and profitability increase, then the capital structure is more appropriate.